2001
DOI: 10.3989/scimar.2001.65s241
|View full text |Cite
|
Sign up to set email alerts
|

Marine diversity: the paradigms in patterns of species richness examined

Abstract: SUMMARY:The two central paradigms of marine diversity are that there is a latitudinal cline of increasing species richness from poles to tropics and that species richness increases with depth to a maximum around 2,000 m and thereafter decreases. However, these paradigms were based on data collected in the late 1950's and early 1960's. Here I show that the 1960's data, are not representative and thus the paradigms need re-examination. New data from coastal areas in the northern hemisphere record species richnes… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
136
2
3

Year Published

2006
2006
2013
2013

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 171 publications
(152 citation statements)
references
References 100 publications
(119 reference statements)
4
136
2
3
Order By: Relevance
“…Species-accumulation curves (sensu Gray 2001;Fig. 2) show that the Wve replicates sampled were suYcient to include >90% of the soft-sediment species as they already level at 3-4 cores.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Species-accumulation curves (sensu Gray 2001;Fig. 2) show that the Wve replicates sampled were suYcient to include >90% of the soft-sediment species as they already level at 3-4 cores.…”
Section: Resultsmentioning
confidence: 99%
“…Marine species diversity in the northern hemisphere generally declines from low to high latitudes (Thorson 1957;Brattegard and Holthe 1997;Roy et al 1998;Gray 2001). However, environmental and biotope complexity may favour biodiversity on small scale.…”
Section: Introductionmentioning
confidence: 99%
“…Therefore, it seems that the low number of herbivores in Arctic waters is more related to factors such as food quality or physical properties of macroalgae that may influence mesoherbivore diversity and population structure. It has been suggested that the relatively young evolutionary history of the Arctic Ocean (Dayton et al, 1994) contributes to a generally low biodiversity due to a relatively short period for adaptation and speciation (Gray, 2001). Another aspect could be the principal inefficiency of macroalgae as nutritional source (Hessen, 1992;Sterner and Hessen, 1994) (e.g.…”
Section: Herbivores In Kongsfjordenmentioning
confidence: 99%
“…Many hypotheses have been put forward to explain the observed patterns but few causal relationships have been identified (Pianka 1966;Gaston 2000;Hillebrand 2004;Jablonski et al 2006;Harrison and Cornell 2007;Buckley et al 2010). These patterns also exist in the marine benthos (Sanders 1968;Roy et al 1998;Gray 2001;Witman et al 2004), with diversity culminating on tropical coral reefs. Exceptions are however found within some taxa (Hillebrand 2004;Krug et al 2007) and at some high latitude biodiversity hotspots like those created by deep coldwater coral reefs (Jensen and Fredriksen 1992;Freiwald et al 2004).…”
Section: Introductionmentioning
confidence: 99%